Development and validation of a rating curve for the Ganga River at the Varanasi bend - Chauhan M.S.; Omar P.J.; Dikshit P.K.S.; Dwivedi S.B. (My University, 2025)
This research paper focuses on the development and validation of a rating curve for the River Ganga at Varanasi. Traditional methods of measuring gauges and calculating discharge face challenges during floods, necessitating innovative approaches. This study employs acoustic Doppler current profilers (ADCP) and remote measurement techniques, addressing the limitations of conventional methods. The methodology involves a two-step procedure: establishing the stage–discharge relationship and measuring the stage for discharge determination. The results highlight the importance of the proposed rating curve equation as a valuable tool to predict river discharge during flood conditions at the Varanasi bend. Ongoing checks are emphasized due to evolving stream channels, affirming the equation's reliability for practical applications. This study contributes to advancing river discharge estimation techniques, particularly in challenging environments like floods. The proposed rating curve equation proves effective and reliable, showcasing its potential for broader applications in hydrological studies and river management. © 2025 The Authors.